A Study of Structural Functionalism on A musical group named Nasida Ria - Falah, Ade Fajrul; Utomo, Udi; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2019)
Nasida Ria is a popular modern qasidah group and has popular songs in the society. This group was born as a form of a group's expression and as a communication media among those people having a preaching mission through the media of arts, that is music. Nasida Ria was founded by KH. Muhammad Zain, and for almost 4 decades, the group has been established and still exists until now. The typical characteristic of the musical performance of modern Qasidah of Nasida Ria is the nine woman musicians who wears hijab. The problem of the research discussed in this writing will focus on the study of how structural functionalism works on the group, Nasida Ria. The methodology of the research applied will be qualitative method with an sociological approach to art through the theory of structural functionalism. The techniques of collecting data used on the research will be observation, interview, and document study. Then, the data validity will be checked by applying triangulation method and continued with data reduction, data presentation, and the drawing of conclusion. According to Robert K. Merton every element of a group will have a function, a dysfunction, a latent function, a manifest function, and an effort to reach the balance. The result of the research shows that the continuation of Nasida Ria is because every part or structure of the group has been functional to each other. The parts of the group are the manager, song composer, music players, and fans. However, there is also a dysfunction in the group, Nasida Ria, i.e. in the regeneration process of the group. Even so, with the feeling as a family attached to every personnel of the group, such dysfunction can be well overcome. Therefore, the balance and the integrity of the group can be developed continuously. The hope of the fans that Nasida Ria will still exist and have a new album is its manifest function, whereas its latent function, the unexpected function, is the discontinuation of Nasida Ria group.